WHAT DROVE THE AMERICAN DECISION TO THE NATO BOMBING OF YUGOSLAVIA IN 1999? - Lošić, Goran (Political Review, 2024)
This paper discusses relations between American branches of power and the NATO bombing of Yugoslavia in 1999. Primarily, the focus is on U.S. President Bill Clinton’s official statements, administration staff, and members of U.S. Congress. The aim is to analyze dominant arguments, political discourse, and narratives about the military operation against Yugoslavia. The work addresses a central analytical question: What drove the American decision to the NATO military action against Yugoslavia in 1999? In other words, the research intends to dig into who was involved in the military campaign from the part of American branches of power and who was against it. The work consists of three parts; the first provides a short contextual framework with the conceptual and theoretical background; the paper then looks at President Clinton’s central arguments for initiating the war. In the last part, the article presents specific reflections regarding the justification of bombing and opinions against it in the U.S. Congress. As a methodology tool, the work utilizes content analysis. The sources are based on the BBC, CNN, Washington Post, New York Times, Wall Street Journal, Guardian, and Los Angeles Times texts, on NATO and Clinton Foundation online data, Clinton Digital Library Archive and U.S. Congress (House of Representatives and Senate) records.